Pengaruh Kegiatan Matrikulasi Pendidikan Seks dan Kesadaran tentang Bahaya Pornografi terhadap Karakter Peserta Didik - Gunawan, Agus (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2016)
This research article found three conclusions as follows: First, the activities of sex education matriculation significant positive effect on the student character of the Madrasah Ibtidaiyah Darwata. This is evidenced by Pearson Product Moment correlation test which resulted in a coefficient of 0.653 (high or strong correlation). Thus, the first hypothesis which states that the activities of sex education matriculation significant positive effect on the character of the students are accepted. The more optimal matriculation activities of sex education, the better the character of the students. Secondly, awareness about the dangers of pornography significant positive effect on the student character of the Madrasah Ibtidaiyah Darwata. This is evidenced by Pearson Product Moment correlation test which resulted in a coefficient of 0.629 (high or strong correlation). Thus, the second hypothesis which states that the awareness about the dangers of pornography significant positive effect on the character of the students are accepted. The higher the students' awareness of the dangers of pornography, the better the character of the students. Third, the two variables, variables matriculation activities of sex education and awareness about the dangers of pornography variables jointly significant positive effect on the student character of the Madrasah Ibtidaiyah Darwata. This is proved by the test that produces multiple correlation coefficient of 0.773 (correlation is very high or very strong). Thus, the third hypothesis which states that the activities of sex education and matriculation students' awareness about the dangers of pornography together significant positive effect on the character of the students are accepted. The more optimal matriculation activities of sex education and the higher the students' awareness of the dangers of pornography, the better the character of the students.